Analysis of Cadmium Metal in Facial Moisturizing Cream with Atomic Absorbtion Spectrophotometry Method - Ardhya, Hilda; Wardah, Annisa Chiyarotul; Rachmawati, Pipit (Indonesian Journal of Chemistry and Environment, 2017)
This study aims to determine the concentration of cadmium (Cd) metal content in various facial moisturizing creams with atomic absorbtion spectrophotometry (AAS). Samples were analyzed in the form of 6 brands of facial moisturizer cream that sold in market and selected randomly. The cream samples were destructed by wet destruction method. Next, the samples of destruction result were analyzed by atomic absorbtion spectrophotometry method with wavelength about 228.8 nm to determine the concentration of cadmium. The results of this research showed that there was cadmium (Cd) metal content in the 2 samples of facial moisturizing cream that analyzed. Cadmium metal concentration on brand A is 0.1389 ± 2.7817 x 10-3 ppm and and brand B is 0.1321 ± 2.6468 x 10-3 ppm. Based on this result, the moustirizing creams are safe to use due to the BPOM regulation